AB0482 Similar efficacy of tofacitinib on disease activity in rheumatoid arthritis patients with and without previous biologicals; results from the turkbio registry. (12th June 2018) - Zengin, B.; Inanç, N.; Akar, S.; Can, G.; Dalkilic, E.; Tufan, A.; Senel, S.; Serdar Koca, S.; Capar, S.; Yarkan Tugsal, H.; Birlik, M.; Akkoc, N.; et al.
Abstract : Background: The aim of this study was to investigate the drug survival, its efficacy and safety in patients withRA based on the database from the Turkish TURKBIO registry Methods: A total of 180 patients were treated with TOFA forRA. Drug survival was assessed. In 118 patients with available data, treatment response was evaluated using thenumber of sensitive and swollen joints, VAS values, DAS28, HAQ and CRPat weeks 12, 24, 48 and 60 Results: At baseline, RA patients had a median(Q1-Q3)disease duration of 14 years.75 patients had used ≥1 biologics previously. The other demographic and clinical features of the patients were shown in table 1. Median(Q1-Q3)followup period was137 weeks. After48 and137 weeks, 75% and 48%of the patients respectively, maintained TOFA (figure 1). The most common reason for drug discontinuation was ineffectiveness of treatment(63%), followed by adverse events (23%). After 12 weeks, all disease activity parameters were reduced significantly compared to the baseline and most of them continued to be reduced until week60. No difference was observed in disease activity parameters between the groups with and without previous ≥1biologics at weeks 0, 12 and 24 (table 2) Remission rate was(43%)at week 60(observed data) (table 2) A total of 9 adverse events(3infection, 3allergic rx, 2 rash)were observed during the followup period Conclusions: Treatment with TOFA may provide good response rates in RA patients refractory previous biologicals Disclosure of Interest: None declared